FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN NELAYAN DI DENPASAR SELATAN - Juliani, Ni Kadek; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 5 (2022): VOL 11 NO 5, MEI 2022 [1621-2044]DO - 10.24843/EEP.2022.v11.i05.p15, 2022)
This study analyzes the effect of working capital, work intensity, and work experience simultaneously on fishermen's income; the effect of venture capital, work intensity, and work experience on fishermen's income; work experience in moderating the influence of work intensity on fishermen's income in South Denpasar. The number of samples in this study is 89 people from 804 populations and analyzed using Moderation Regression Analysis. Based on the results business capital, work intensity, and work experience affect the income of fishermen in South Denpasar. Business capital, work intensity, and work experience simultaneously influence the income of fishermen in South Denpasar. Business capital, work intensity, and work experience have a partial positive effect on fishermen's income in South Denpasar. Work experience strengthens the effect of work intensity on fishermen's income in South Denpasar. keyword : venture capital, work intensity, work experience, income. JEL: E22, J20, J21 , D33